Communication Strategies Used By EFL Students in English Classroom Setting - Rahman, Arif; Isroyana, Dian Novia (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2021)
The main objective of teaching English is to allow the learner to communicate orally and successfully. People all over the place study a foreign language to enable them to communicate effectively. This study investigates a phenomenon about communication strategy used by EFL students in English Classroom Setting. The focus of this study is to investigate the types of communication strategies and the most frequent types of communication strategies employed by EFL Students. It took place in Institut Pendidikan Nusantara Global that located in Central Lombok. The participant of this study was a total of 20 students from the second semester. A qualitative research design was used to collect the data need in this study embarrassing interviews and observation as main instruments; the observation used were field notes and videotape aimed to get the documentation of the study. The finding of the study shows that most of the students employed the types of communication strategy i.e.: Asking for clarification, requesting an explanation, asking for repetition, circumlocution, message abandonment, meaning negotiation, and interaction monitoring. Furthermore, the communication strategies frequently used by students i.e.: asking for clarification, message abandonment, and meaning negotiation. In conclusion, every student has their own communication strategy but the researcher categorized those strategies into several types.